PERILAKU KURANG GERAK (SEDENTARY BEHAVIOUR) DENGAN PERKEMBANGAN PSIKOSOSIAL ANAK PRA SEKOLAH - Ludyanti, Laviana Nita (Universitas Tribhuwana Tunggadewi, 2019)
The development of science and technology, creates various kinds of conveniences that cause an increase in sedentary behavior. This also has an impact on the development of pre-school age children, one of which is psychosocial development. This study aims to determine the relationship between sedentary behaviour and psychosocial development in pre-school children. The design of this study is correlational with a cross sectional approach. The population in this study were mothers of pre-school age children at ABA II Kindergarten, with a sample of 35 people using purposive sampling techniques. Its collected with quessionaire. Statistical analysis using a Spearman Rank Test with α = 0.05. The results showed that most children had psychosocial development in the not appropriate category of 71%. While the lack of motion behavior in the heavy category was 77%. The results showed that there was a significant relationship between sedentary behavior and psychosocial development in pre-school children with results (r = 0.457; ρ = 0,00